The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0004-282x2003000200031
|View full text |Cite
|
Sign up to set email alerts
|

Expensive cerebral blood flow measurements alone are useless and misinformative in comatose patients: a comprehensive alternative

Abstract: -Since the first report addressing quantification of cerebral blood flow (CBF), concomitant assessment of cerebral oxygen consumption was also carried out. Over the years, however, some investigators have emphatically and mistakenly addressed cerebral ischemia in comatose patients, on the basis of CBF measurements alone. In contrast, we have repeatedly reported that ischemia in these patients must be precisely evaluated based on CBF-metabolism coupling or uncoupling, rather than CBF alone. Based on these previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The classic work of Obrist and colleagues 32 shows how patients with low flow pattern achieve near-normal values of arteriovenous oxygen difference (DavO 2 ), however, patients with hyperemic pattern show DavO 2 below the limits of normality. The article by Obrist et al 32 and more recently that of Cruz et al 33 , have shown that the worst result is given by the decoupling between cerebral blood flow (CBF) and cerebral metabolic rate of O 2 (flow -metabolism), with unfavourable results associated with hyperemic patterns.…”
Section: Cerebral Hemodynamics By Transcranial Doppler and Protein S1mentioning
confidence: 99%
“…The classic work of Obrist and colleagues 32 shows how patients with low flow pattern achieve near-normal values of arteriovenous oxygen difference (DavO 2 ), however, patients with hyperemic pattern show DavO 2 below the limits of normality. The article by Obrist et al 32 and more recently that of Cruz et al 33 , have shown that the worst result is given by the decoupling between cerebral blood flow (CBF) and cerebral metabolic rate of O 2 (flow -metabolism), with unfavourable results associated with hyperemic patterns.…”
Section: Cerebral Hemodynamics By Transcranial Doppler and Protein S1mentioning
confidence: 99%